Comunicación estratégica para el ejercicio del liderazgo femenino - Fuentes Rodríguez, Catalina; Brenes Peña, Ester (Taylor & Francis, 2023)
This edited collection brings together corpus-based research to provide a detailed analysis of gender and the discourse of women leaders or professionals in domains historically dominated by men, such as business, science, media and politics. Based on the analysis of real texts, the volume seeks to determine which traits are truly characteristic of feminine discourse, how women who have been successful in these domains have used their discourse to create and project their own identity, and what conclusions can be drawn regarding the characteristics of the discourse of successful female leaders. It incorporates a diachronic perspective that helps us understand the evolution of the role and discourse of and about women. The collection will be of interest to researchers in Spanish Applied Linguistics, Hispanic Sociolinguistics and Communication and Gender Studies.